(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The present paper starts out from the pragma-dialectic model in order to analyze and explain the polemic held by the newspapers El Ómnibus, El Siglo xix and La Cruz in pieces of writing by the Catholic journalists Juan Bautista Morales (moderate liberal) and José Joaquín Pesado (conservative), between October 1855 and April 1856. The article also reveals certain similarities of structural character in the line of argumentation between conservative and liberal newspapers, which appear through their use of fallacies.